2010
DOI: 10.1016/j.pharmthera.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets and mechanisms for ethanol action in glycine receptors

Abstract: Glycine receptors (GlyRs) are recognized as the primary mediators of neuronal inhibition in the spinal cord, brain stem and higher brain regions known to be sensitive to ethanol. Building evidence supports the notion that ethanol acting on GlyRs causes at least a subset of its behavioral effects and may be involved in modulating ethanol intake. For over two decades, GlyRs have been studied at the molecular level as targets for ethanol action. Despite the advances in understanding the effects of ethanol in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 210 publications
(325 reference statements)
0
49
0
Order By: Relevance
“…However, prior work in recombinant systems found no differences between homomeric ␣1 GlyRs and heteromeric ␣1␤ GlyRs in responsiveness to glycine (Lynch, 2004). More important, homomeric ␣1 GlyRs have been the primary focus of molecular modeling studies (Webb and Lynch, 2007;Perkins et al, 2010). Therefore, we used homomeric ␣-1 GlyRs in the present study.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, prior work in recombinant systems found no differences between homomeric ␣1 GlyRs and heteromeric ␣1␤ GlyRs in responsiveness to glycine (Lynch, 2004). More important, homomeric ␣1 GlyRs have been the primary focus of molecular modeling studies (Webb and Lynch, 2007;Perkins et al, 2010). Therefore, we used homomeric ␣-1 GlyRs in the present study.…”
Section: Methodsmentioning
confidence: 96%
“…Those studies found that behaviorally relevant concentrations of ethanol positively modulate GlyR function measured in a variety of preparations (for review, see Perkins et al, 2010). Other studies suggest that GlyRs in the nucleus accumbens are targets for ethanol that are involved in ethanol-induced mesolimbic dopamine release (Molander and Söderpalm, 2005;Molander et al, 2007), thus linking GlyRs to the rewarding effects of ethanol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This major class of receptor channels passes either anions, such as the g-aminobutyric acid A (GABA A ) and strychninesensitive glycine receptors, or cations, such as the nicotinic acetylcholine nACh and serotonin 5-HT 3 receptors. The general action of acute ethanol is to enhance the function of cys-loop ligand-gated ion channels (Lovinger, 1997;Harris, 1999;Perkins et al, 2010), although ethanol can also produce inhibition in some subtypes/receptor domains (Johnson et al, 2012). Ethanol exerts its action by potentiating channel opening in the presence of low agonist concentrations.…”
Section: Neural Adaptations Induced By Ethanolmentioning
confidence: 99%
“…Generally, acute EtOH exposure enhances the function of cys-loop LGICs (Aguayo et al 2002;Harris 1999;Lovinger 1997;Perkins et al 2010), but instances of inhibition of the nAChRs and GABA A Rs have been reported (Aguayo et al 2002;Cardoso et al 1999;Davis and De Fiebre 2006;Marszalec et al 1994;Roberto et al 2003). The most common EtOH action is to potentiate channel opening in the presence of a low concentration of agonist by increasing the probability of channel opening (Zhou et al 1998), and/or increasing agonist affinity (Tonner and Miller 1995;Welsh et al 2009).…”
Section: Ligand-gated Ion Channels and Postsynaptic Ethanol Effectsmentioning
confidence: 99%